Shale Gas Exploration Potential in Southwestern Shandong Province of Eastern China - Cuifang, Li; Xinglong, Huang; Yubao, Shao; Fengke, Dou (Frontiers in Earth Science, 2021)
The shale layers of the Permian Shanxi Formation and Taiyuan Formation in the southwestern part of Shandong Province are marine-continental transitional sedimentary facies. When compared with the Ordos Basin, which was a typical breakthrough in marine-continental transitional shale gas exploration, the geological characteristics, exploration, and development prospects of marine-continental transitional shale gas in the southwestern section of Shandong Province are more defined. The shale gas deposits of the Shanxi and Taiyuan Formations in southwestern Shandong Province have the following geological characteristics. The sedimentary environments of Shanxi and Taiyuan Formations are considered to be stable and characterized with widely distributed organic-rich shale, which can be used as composite evaluation layers. The total thickness of the shale range is between 140 and 350 m, with an average of 230 m. The main types of organic matter in the Shanxi Formation are Type Ⅲ and Type Ⅱ2 kerogen, while the main types of organic matter in the Taiyuan Formation are rock types. The abundance and maturity of the organic matter are high, and the gas generating capacity is strong. The reservoir rock mineral composition is complex in the region. The clay mineral content is relatively high and the brittle mineral content is rich. Also, the shale fracturing ability is good. The region has the characteristics of a low porosity and low permeability reservoir, with relatively good reservoir capacity. Three primary points of interest have stably been developed within the region, which are located in the upper high water level system, near the initial flood surface, and the majority of flood surface, including a transgressive system tract and high level system tract. The total gas content is estimated to range between 0.03 and 4.47 m3/t, with an average of 0.30 m3/t. The shale gas resources are rich, including one favorable Class I location with an area of 819.06 km2 and a resource amount of 985.84 × 108 m3; four favorable Class Ⅱ locations with an area of 1,979.68 km2 and a resource amount of 2,278.14 × 108 m3; and five prospective locations with an area of 8,385.52 km2 and a resource amount of 7,299.48 × 108 m3. Therefore, the region was considered to have major exploration potential.